Altered Immune Activation and IL-23 Signaling in Response to Candida albicans in Autoimmune Polyendocrine Syndrome Type 1 - Bruserud, Øyvind; Bratland, Eirik; Hellesen, Alexander; Delaleu, Nicolas; Reikvam, Håkon; Oftedal, Bergithe E.; Wolff, Anette S. B. (Frontiers in Immunology, 2017)
Objective Autoimmune polyendocrine syndrome type 1 (APS-1) is a rare, childhood onset disease caused by mutations in the Autoimmune regulator gene (AIRE). Chronic mucocutaneous candidiasis (CMC) is one of the three major disease components and is, to date, mainly explained by the presence of neutralizing auto-antibodies against cytokines (interleukin-17A (IL), IL-17F and IL-22) from T helper 17 (Th17) cells, which are critical for the protection against fungal infections. However, patients without current autoantibodies also present CMC and we therefore hypothesized that other immune mechanisms contribute to CMC in APS-1. Methods Whole blood was stimulated with Candida albicans (C. albicans) in a standardized assay and immune activation was investigated by analyzing 46 secreted immune mediators. Then, peripheral blood mononuclear cells (PBMCs) were stimulated with curdlan, a dectin-1 agonist and IL-23 inducer, and the IL-23p19 response in monocytes was analyzed by flow cytometry. Results We found an altered immune response in APS-1 patients compared with healthy controls. Patients fail to increase the essential interleukins IL-2, IL-17A, IL-22, and IL-23 when stimulating whole blood with C. albicans. A significantly altered IL-23p19 response was detected in patients’ monocytes upon stimulation with curdlan. Conclusions APS-1 patients have an altered immune response to C. albicans including a dysregulation of IL-23p19 production in monocytes. This probably contributes to the selective susceptibility to CMC found in the majority of patients.